2022
DOI: 10.1093/ntr/ntac174
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and Postnatal Cocaine Enhances the Induction and Expression of Locomotor Sensitization to Nicotine in Male Rats

Abstract: Introduction Several studies mention that early consumption of cannabis, alcohol, or even cocaine is related to an increase in the prevalence of daily consumption of tobacco in adulthood. However, other factors, such as genetic comorbidity, social influences, and even molecular, neurochemical, and behavioral alterations induced by prenatal and postnatal cocaine exposure, could also explain these observations, since these factors together increase the vulnerability of the offspring to the rein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In rodents, the prenatal and postnatal cocaine exposure dose‐dependent enhanced locomotor activity and cocaine‐ or nicotine‐induced locomotor sensitization (Barbosa‐Méndez & Salazar‐Juárez, 2020, 2022; Crozatier et al., 2003; Magalhães et al., 2005; Sobrian et al., 2008). These studies suggest that prenatal and postnatal cocaine exposure increases cocaine salience (Barbosa‐Méndez & Salazar‐Juárez, 2020, 2022; Sobrian et al., 2008), supporting the hypothesis that perinatal cocaine exposure increases offspring's vulnerability to cocaine's reinforcing and psychomotor effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rodents, the prenatal and postnatal cocaine exposure dose‐dependent enhanced locomotor activity and cocaine‐ or nicotine‐induced locomotor sensitization (Barbosa‐Méndez & Salazar‐Juárez, 2020, 2022; Crozatier et al., 2003; Magalhães et al., 2005; Sobrian et al., 2008). These studies suggest that prenatal and postnatal cocaine exposure increases cocaine salience (Barbosa‐Méndez & Salazar‐Juárez, 2020, 2022; Sobrian et al., 2008), supporting the hypothesis that perinatal cocaine exposure increases offspring's vulnerability to cocaine's reinforcing and psychomotor effects.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, given that (1) prenatal and postnatal cocaine exposure increases the vulnerability of offspring to cocaine effects (Barbosa‐Mendez & Salazar‐Juárez, 2022), (2) emotional (anxiety and depression) disorders that occur during withdrawal also increase the risk of relapse of cocaine abuse (Conway et al., 2006; Grant et al., 2004), (3) the history of cocaine withdrawal symptoms may be associated with better cocaine responses and greater severity of cocaine dependence (Sofuoglu et al., 2006), and (4) to our knowledge no longitudinal study has been reported to assess the effects of prenatal and postnatal cocaine exposure on anxiety and depression‐like behaviors during cocaine withdrawal; Therefore, the objective of this study was to characterize anxiety‐ and depression‐like behaviors at different times (1, 30, 60, 90, and 120 days) of cocaine withdrawal in rats born to females exposed prenatally and postnatally to cocaine. To do this, we use several behavioral tools to determine anxiety‐ and depression‐like behaviors.…”
Section: Introductionmentioning
confidence: 99%